Juan Villar, Arte de gramática española. Est. introd. de Manuel Peñalver Castillo. Ed. facs. Diputación Provincial de Jaén, Jaén, 1997; 119 + 159 pp. - Valadez, Carmen Delia (El Colegio de México, 2000)
Se reseñó el libro: Arte de gramática española.